2007
DOI: 10.1088/0967-3334/28/4/005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high concentration oxygen administration onn-back task performance and physiological signals

Abstract: This study investigated the effect of 40% oxygen administration on n-back task performance, blood oxygen saturation and heart rate. Five male (25.8 +/- 1.3 years) and five female (23.0 +/- 1.0 years) college students were selected as the subjects for this study. The experiment consisted of two runs: one was an n-back task with normal air (21% oxygen) administered and the other was with hyperoxic air (40% oxygen) administered. The experimental sequence in each run consisted of Rest1 (1 min), 0-back task (1 min)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 13 publications
8
28
1
8
Order By: Relevance
“…Previous studies reported that HR during the cognitive task phases increased over the rest phase [4,[6][7][8][9]19,20]. This study also showed that HR increased in the visual matching task phase over the rest phase.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Previous studies reported that HR during the cognitive task phases increased over the rest phase [4,[6][7][8][9]19,20]. This study also showed that HR increased in the visual matching task phase over the rest phase.…”
Section: Discussionsupporting
confidence: 77%
“…In order to metabolize the fuel, the brain needs more oxygen [13]. Therefore, oxygen demand increases during cognitive processing period and this induces an increase in HR [4,[6][7][8][9]19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consideration of both inward and outward information flow is a common strategy, however, in some areas of science, for example, in ecology, where organisms are considered in terms of environmental inputs and outputs, and neuroscience, where information transfer into and out of neuronal synapses is integral to studies of information flow. Studies based in integrative biology lend support to a contention that there is a significant effect on learning due to input and output information flow of even simple, but often overlooked, environmental factors, such as water, oxygen and glucose [33,34]. It follows, therefore, that learning principles derived from a broader sense of information flow may apply to teaching and instructional design in relation to organisation of environmental input and outputs.…”
Section: Analysis Of Findingsmentioning
confidence: 94%